VINASSE EFFECT ON HERBICIDES CLOMAZONE AND TEBUTHIURON AVAILABILITY IN DIFFERENT KINDS OF SOILS - MATOS,A.K.A. (2015)
ABSTRACT The objective of this study was to evaluate the availability of herbicides clomazone and tebuthiuron in the solution in different kinds of soils saturated with water or vinasse. Samples of 30 soils with different characteristics were arranged on trays to the herbicides spraying. Then they were homogenized, placed in plastic cartridges and saturated with deionized water or vinasse, and remaining at rest during 18 hours. Two extractions were made, the first one quantified the presence of the herbicides in the soil solution and in the second one the total extraction of herbicide remaining in the soil was taken to determine the recovery percentage of each herbicide tested. For quantification, a LC-MS/MS system was used, a compound of a high performance liquid chromatograph (HPLC) coupled to a triple quadruple mass spectrometer. Tebuthiuron was more available in the soil with the vinasse addition when compared to water. Vinasse applications resulted in no significant difference in availability of clomazone between treatments. Tebuthiuron showed the highest availability frequencies, and on average of all samples 32.49% were extracted from total herbicide applied, while for clomazone this value was 16.50%.